Anatomic study of the profunda artery perforators by multidetector CT scanner and clinical use of the banana‐shaped flap design for breast reconstruction. Issue 2 (5th October 2021) - Zeltzer, Assaf A.; Waked, Karl; Brussaard, Carola; Giunta, Gabriele; De Baerdemaeker, Randy; Hamdi, Moustapha
Abstract: Background: The profunda artery perforator (PAP) flap is a well‐known free flap for breast reconstruction. However, a reproducible perforator mapping system has yet to be developed. Methods: The PAP perforators were localized by CTA using a novel X ‐ Y axis system. Flap dimensions were based on the CTA images and localized PAP‐perforators. Perioperative findings and postoperative outcomes were analyzed. Results: A total of 70 lower limbs and 180 PAP perforators were evaluated. An average of 2.78 ± 1.22 and 2.22 ± 0.96 perforators were seen, in the right and left legs, respectively, and were divided in five clusters (PAP1–PAP5) based on their location on the Y ‐axis. The course of the perforators was noted as well as the average diameter at the origin. The overall average diameter was 1.99 ± 0.86 mm. A banana‐shaped PAP‐flap was harvested in 10 patients. The mean operative time was 278 min, pedicle length 76 ± 12 mm, and mean flap weight 247 g. No major complications were seen. Conclusion: The PAP flap can be mapped by CTA in a reproducible way. The X and Y axes are based on fixed anatomic landmarks and may form the basis for a banana‐shaped flap design of the PAP‐flap.